Age- and Time-Related Trends in Oral Health Care for Patients Aged 60 Years and Older in 2007-2017 in Public Oral Health Services in Helsinki, Finland - Kaija Hiltunen; Päivi Mäntylä; Miira M. Vehkalahti (Elsevier, 2021)
Background: Population aging will likely have an impact on oral health care trends. The aim of this study was to describe age- and time-related trends in oral health care in people ages 60 and older in Public Oral Health Services (POHS) in Helsinki, Finland. Materials and methods: Material for the study comprised the electronic documentation of oral health care procedures performed on patients 60 years and older (N = 282,143) in POHS during 2007-2017. Patients were aggregated into 5-year age groups. The 5 most common treatment categories, restorations, periodontal treatment, extractions, endodontics, and prosthetics, were selected for analysis. Changes by time (calendar year) and differences by age group were shown as percentages and percentage points; corresponding trends were assessed by applying linear regression models to the data. Results: The attendance rate for these patients increased from 14.5% in 2007 to 23.1% in 2017, with the total number of visits increasing by 76.4% in the 11-year period. The average number of visits per patient decreased from 3.5 visits in 2007 to 3.0 visits in 2017. In 2007, 60.5% of patients received restorative treatment and 41.3% received periodontal care. In 2017, the corresponding figures were 55.5% and 49.8%, respectively. The older the patient, the fewer the visits and restorative, periodontal, and endodontic treatments and the greater the rate of tooth extractions and prosthetics. Conclusion: A declining age group-related trend was recognized for restorative, periodontal, and endodontic treatments. Owing to ongoing population growth, POHS will be facing huge challenges in providing treatment for all individuals seeking services.